2009
DOI: 10.1124/jpet.109.151233
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Farnesoid X Receptor Signaling Pathway by the Thiazolidinediones

Abstract: Thiazolidinediones (TZD), including troglitazone, rosiglitazone, and pioglitazone, are agonists of peroxisome proliferator-activated receptor (PPAR)-␥ and belong to a class of insulin-sensitizing drugs for type 2 diabetes mellitus. However, memberspecific, PPAR␥-independent activities and toxicity have been reported, especially for troglitazone. Currently, the underlying mechanisms are not fully understood. In this study, we demonstrated that troglitazone but not rosiglitazone or pioglitazone modulated express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 44 publications
(53 reference statements)
0
36
2
Order By: Relevance
“…2C, at higher concentrations, both lopinavir and troglitazone significantly reduced the FXR activity that was preinduced by CDCA, a known endogenous activator of FXR. Intriguingly, a previous report revealed that in Huh7 cells, although troglitazone (10 mM) moderately induces the basal expression of BSEP, it dose dependently represses CDCA-induced BSEP mRNA in a FXR-dependent manner (Kaimal et al, 2009). In contrast, benzbromarone, bosentan, or glimepiride exhibited only negligible effects on FXR activity (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…2C, at higher concentrations, both lopinavir and troglitazone significantly reduced the FXR activity that was preinduced by CDCA, a known endogenous activator of FXR. Intriguingly, a previous report revealed that in Huh7 cells, although troglitazone (10 mM) moderately induces the basal expression of BSEP, it dose dependently represses CDCA-induced BSEP mRNA in a FXR-dependent manner (Kaimal et al, 2009). In contrast, benzbromarone, bosentan, or glimepiride exhibited only negligible effects on FXR activity (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…One provocative study found that troglitazone can bind the FXR ligand binding domain. This effect was postulated to be mediated through the tocopherol side chain that is unique to troglitazone among the thiazolidinediones and this inhibitory interaction of troglitazone has been postulated to explain its idiosyncratic hepatotoxicity [13].…”
Section: Fxr Ligandsmentioning
confidence: 99%
“…Human, mouse, and rat bsep promoter reporters and mutants, including phBSEP (-2.6kb), pmBSEP(-2.6kb), prBSEP(-2kb), phBSEP(-125b), and phBSEP(-2.6kb)-IR1a-Mut, were prepared previously ( 18,28,29 ). Human pTK-3xhIR1a, mouse/rat pTK3xm/rIR1a, and pTK-3xIR1b reporters were constructed by cloning three copies of the corresponding element into pTK-Luc vector.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…Mutations were introduced into the templates using a QuickChange site-directed mutagenesis kit according to the manufacturer's manual (Stratagene) ( 29 ). Human BSEP promoter mutants phBSEP(-2.6kb)-IR1b-Mut, phBSEP(-2.6kb)-IR1ab-Mut, and phBSEP(-2.6kb)-ER2-Mut were prepared by mutating the IR1b, IR1a and IR1b, and half ER2 (everted repeat separated by two nucleotides) sites using phBSEP(-2.6kb) as a template.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%